Democratic Republic of Congo Reforming the Public Service Wage System : Background Paper - World Bank (Washington, DC, 2014)
The civil service management model in the Demorcatic Republic of Congo (DRC) still conforms to the old institutional order. The legislation governing employment in the public sector is unchanged and still responds to centralized administration. The public administration categorizes public employees in two main groups: civil servants and local public employees. Civil servants are governed by legislation that is neither merit based nor performance and result oriented. Local public employees are governed by labor legislation. Decentralization also requires the definition of a salary system for the new provincial administrations. For the first six months of the establishment of the provincial Civil Service, the same salary paid to the State civil servants should be ensured and paid to the provincial civil servants by the State administration. The provinces would not have yet established adequate financial coverage and mechanisms to ensure regular payments. While the provincial administrations are being consolidated (maximum 2 years), new legislation for public sub national service should be established including norms on wages. Such legislation should be in line with the national civil service legislation regarding principles and standards. The DRC Government is faced with five main challenges: 1) To modernize the Civil Service system and amend its legislation to elevate it to improved standards of efficiency in service delivery and human resources management. These can be achieved by instilling values including merit, results, performance, and professionalization. 2) To fill the normative vacuum by setting rules and procedures to manage the new decentralized Civil Service. 3) To establish interactive consultation tools and procedures among all levels of public administration. 4) To harmonize the national and sub-national Civil Services with the new constitutional order. 5) To make the public administration a more attractive employer for young skilled professionals by reforming and improving the public sector wage system through systematic and sound reform measures.